Y+4.7=-8.6-5.3

Simple and best practice solution for Y+4.7=-8.6-5.3 equation. Check how easy it is, and learn it for the future. Our solution is simple, and easy to understand, so don`t hesitate to use it as a solution of your homework.

If it's not what You are looking for type in the equation solver your own equation and let us solve it.

Solution for Y+4.7=-8.6-5.3 equation:


Simplifying
Y + 4.7 = -8.6 + -5.3

Reorder the terms:
4.7 + Y = -8.6 + -5.3

Combine like terms: -8.6 + -5.3 = -13.9
4.7 + Y = -13.9

Solving
4.7 + Y = -13.9

Solving for variable 'Y'.

Move all terms containing Y to the left, all other terms to the right.

Add '-4.7' to each side of the equation.
4.7 + -4.7 + Y = -13.9 + -4.7

Combine like terms: 4.7 + -4.7 = 0.0
0.0 + Y = -13.9 + -4.7
Y = -13.9 + -4.7

Combine like terms: -13.9 + -4.7 = -18.6
Y = -18.6

Simplifying
Y = -18.6

See similar equations:

| -4x+6-5(x-1)=-(3x-3)-5x+5 | | X-0.2=6.4 | | 5x-2(3-4x)=3(x-3)-57 | | (4f^2-3)+11f=0 | | 5x+18+3x+34=90 | | y-7=-2.66(x-10) | | 42y+16= | | 4(2x+2)+5=3+2(4x+5) | | Z-2.8=10.9 | | Y/0.2=0.8 | | 16a^2+24ab+9b=(a+3b) | | (8x-8)/7=-8 | | y-7=0.66(x-10) | | 8=2v | | 2-(2x+3)=-11 | | 6x+5=5x+11 | | 0.5a=1.5 | | 3y-8+y+56=6y+50-4y | | (-3/4)²x | | 0.09xX=78.73 | | 12x+5=8x-17 | | 3m+5m=10 | | (-3/4)²*x | | 2x+7y=33.00 | | (-3/4)² | | -5+x=2y | | -43+5y+4=3(3y-3)-6 | | -48+4x=x | | 2-5-14=0 | | v-8.48=7.92 | | 45=v/3 | | 9+y=28 |

Equations solver categories